Implementasi Model Guided Discovery Learning dalam Mata Pelajaran Dasar Ketenagalistrikan - Afdal Yusra; Elfizon Elfizon (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
This study investigates the effectiveness of implementing the Guided Discovery Learning model in improving student learning achievements within the Fundamentals of Electrical Power course for tenth-grade learners specializing in Electrical Power Installation at a vocational high school in Padang, Indonesia. The research adopts a quantitative methodology featuring a one-group pretest-posttest design, where participants engaged with a validated multiple-choice assessment tool confirmed reliable via product-moment correlation and internal consistency checks. Descriptive statistics, normalized gain calculations, the Wilcoxon signed-rank test, and effect size analysis were applied to evaluate improvements. Findings reveal a marked enhancement in post-intervention scores compared to initial assessments, with normalized gains predominantly falling into moderate categories, alongside a subset achieving higher levels and a smaller portion showing lower progress. The Wilcoxon test indicates statistically significant differences between pre- and post-scores, while the effect size points to a substantial influence. These results affirm that Guided Discovery Learning effectively bolsters conceptual understanding of electrical principles, fosters active engagement, reduces learning disparities among vocational students, and promotes a more equitable classroom dynamic. Consequently, this student-centered approach is recommended as a viable alternative to traditional teacher-led methods in vocational settings, particularly for technical subjects like electrical fundamentals, to better align education with industry demands and enhance practical problem-solving skills.